2017
DOI: 10.7861/clinmedicine.17-4-380
|View full text |Cite
|
Sign up to set email alerts
|

Sleep awareness and education among clinical practitioners

Abstract: References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It was hypothesized that questionnaire items about knowledge of the importance of sleep, circadian rhythms, and sleep-promoting behaviors might influence sleepscheduling strategies. It has been reported that physicians get approximately 2-3 h of sleep education during their medical training, 43,44 but to our knowledge, exposure to sleep education has not yet been quantified in nurses outside of our studies. 36 We therefore asked several investigator-developed questions regarding the extent of sleep knowledge, motivation to engage in healthy sleep behaviors, and exposure to education regarding sleep and circadian health.…”
Section: Individual Characteristicsmentioning
confidence: 72%
“…It was hypothesized that questionnaire items about knowledge of the importance of sleep, circadian rhythms, and sleep-promoting behaviors might influence sleepscheduling strategies. It has been reported that physicians get approximately 2-3 h of sleep education during their medical training, 43,44 but to our knowledge, exposure to sleep education has not yet been quantified in nurses outside of our studies. 36 We therefore asked several investigator-developed questions regarding the extent of sleep knowledge, motivation to engage in healthy sleep behaviors, and exposure to education regarding sleep and circadian health.…”
Section: Individual Characteristicsmentioning
confidence: 72%
“…Advocacy is an important tool in the implementation of the neurological quadrangle and IGAP 1 to improve neurological services and optimize brain health. Health diplomacy and advocacy and population-wide educational interventions will be pivotal for the prevention of neurological disorders such as CNS infections, epilepsy, sleep disorders and stroke 76 , 77 , 84 , 85 . Given the diversity of neurological disorders, disease-specific advocacy is a common approach to ensure adequate representation, even for rare conditions.…”
Section: Towards Improving Brain Healthmentioning
confidence: 99%